Does Household Financial Management of Independent Oil Palm Smallholders Promote Rural Development? - Nurliza Nurliza; Aditya Nugraha; Morteza Muthahhari; Pamela Pamela (Universitas Muhammadiyah Yogyakarta, 2023)
Sustainable production by independent oil palm smallholders links to the creation of goods and services using processes and systems that are resource-conserving, economically viable, and socially and creatively rewarding for all working people and consumers. However, there is limited efficiency in financial management and low resource allocation for rural finance operations to support the development of rural economies. This study tried to prove whether household financial management promotes rural development using the theories of transaction cost, financial transaction management, public expenditure management, and a rural development framework. This research was conducted in Sambas District, West Kalimantan, using a mixed method with purposive sampling and structured questionnaires administered to 200 independent oil palm smallholders. Multidimensional scaling and a structural equation model were employed to analyze the data. The results unveiled that household financial management promoted rural development due to its effects on accessibility and infrastructure for market opportunities, basic and public services, and governance regarding participation in agriculture meetings and training by the government. Governance emerged as the most direct effect of rural development as it contributed to livelihoods, community-based economic empowerment, human resources, and rural environmental problems. Operational and risk management came as the most influential factors in household financial management. Government played a role in engaging smallholders in supply chains, access to inputs, and households’ transition in confronting a variety of yields, unstable output and input prices, and changes in production technology. Innovative multi-actor collaborations were required to reinforce and provide a cloak for policy decisions.